Beyond recognition: gendered violence and the critique of political economy in Croatia - Kujundžić, Jana (Frontiers in Sociology, 2025)
This paper critiques the understanding of gendered violence solely through the lens of recognition politics without addressing the politics of redistribution in post-conflict, post-socialist Croatia. Since the 1990s, privatization and transition period have eroded social security nets and workers' rights, even as legal reforms and international conventions on victims' protections were incorporated into the Croatian legal system, mainly by EU-funded civil society projects. Persistent underfunding of health, education and social welfare systems undermines meaningful efforts to tackle gendered violence. Drawing on in-depth expert interviews with members of the judiciary, police, social welfare organizations, feminist NGOs, and women's shelters, the paper highlights issues within the legal and social welfare systems through a Marxist-feminist lens. Survivors face the imperative to engage in precarious work, incur significant costs when engaging the legal system, and struggle with limited access to welfare and care services. At the same time, the privileged status of war veterans reinforces social hierarchies and intensifies gendered inequalities. These findings suggest that combating gendered violence cannot be separated from struggles against capitalist exploitation. By connecting recognition and redistribution politics, the paper situates gendered violence within the erosion of post-socialist welfare systems and the persistence of militarized privilege.